Tumor associated macrophages in gastric cancer dual roles in immune evasion and clinical implications for targeted therapy - Wang, Chang; Fan, Xu; Sun, Xiaomen; Xu, Yi; Sun, Yanna; Liu, Jidong (Frontiers in Immunology, 2025)
Gastric cancer (GC) remains a major global health burden with persistently high mortality despite therapeutic advances. Accumulating evidence highlights the pivotal role of tumor-associated macrophages (TAMs) in orchestrating gastric tumor progression through immune suppression, angiogenesis, extracellular matrix remodeling, and metastasis. Within the tumor microenvironment (TME), TAMs exhibit functional plasticity, often polarizing toward an M2-like phenotype that promotes immunosuppression and tumorigenicity. These cells actively participate in immune evasion via immune checkpoint expression and cytokine-mediated T cell inhibition, while also facilitating lymphovascular invasion and chemoresistance through exosome-mediated crosstalk. The density and phenotype of TAMs have been associated with prognosis and therapeutic response in GC. Recent studies have proposed TAMs as promising targets for therapy, with strategies focusing on depleting M2 subsets, reprogramming toward M1 phenotypes, and blocking TAM-driven oncogenic signaling. Targeted interventions, including MENK, paclitaxel, and NF-κB inhibitors, have shown potential in preclinical models. This review comprehensively discusses the mechanistic roles of TAMs in GC and evaluates emerging TAM-targeted therapeutic strategies that may enhance the efficacy of immunotherapy and improve patient outcomes.